Selisih Klaim INA-CBGs dengan Tarif Rumah Sakit Aktual di RS X Surabaya - Pradhana, Andrea Thrisiawan; Yuadi, Imam; Puspitasari, Ira; Djunawan, Achmad; Sholihah, Enny Mar'atus (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2025)
The hospital payment system in Indonesia uses the Indonesia Case Based Groups (INA-CBGs). It is expected to control service costs within the National Health Insurance (JKN) program. However, there is a challenge in the form of a negative difference between BPJS Kesehatan claims and the hospital's actual tariffs. If left unchecked, this could impact the financial sustainability of hospitals. This study aims to predict and analyze the factors influencing the difference between BPJS claims and hospital tariffs at Hospital X Surabaya for the period February to June 2024. The method used is an analytical quantitative study with a time series design using secondary data from BPJS claims and the hospital’s actual tariffs for 6,523 inpatient cases. Data analysis was performed using graphs, cross-tabulation, and multiple linear regression. The results show that the difference between BPJS claims and hospital tariffs is always negative. The largest negative difference occurred in inpatient class 3. Variables such as costs of non-surgical procedure tariffs, surgical procedures, nursing care, supporting services, radiology, laboratory, blood services, rehabilitation, and room accommodation have a significant effect in increasing the claim deficit (p < 0.05). However, drug costs have a significant positive effect in reducing the deficit. The limitation of this study is that the data is not normally distributed and indicates heteroskedasticity. In conclusion, most medical and non-medical cost components contribute to the claim deficit experienced by the hospital during the study period.